Morphological Characterization of the Local Potato (Solanum Tuberosum L.) Genotypes Collected From the Eastern Black Sea Region of Turkey - Arslanoglu, F.; Aytaç, S.; Karaca Öner, E.K. (Academic Journals, 2011)
In this study, 58 villages were selected and a total of 146 samples were taken according to stratified sampling system. These genotypes were collected from production areas in high altitudes of the province of Artvin (41°10' 54"- 40° 49' 09" N and 42° 21' 49"- 41° 32' 40" E) and Rize (41° 02'43"-40° 46' 50" N and 41° 00' 22"- 40° 33' 26" E) located in the Eastern Black Sea region of Turkey. The genotypes were grown under Samsun (41°31′N, 35°35′E) ecological condition in 2006. Some morphological and agronomical characteristics of the genotypes were described according to the criteria developed for potato by the International Board for Plant Genetics Resources (IPBGR). Cluster analysis was performed to determine the relation among genotypes. Cluster analysis, based on 15 variables, identified 27 groups in the current study. The dendrogram was prepared to evaluate similarity between potato genotypes, and as such, all the obtained data showed that the collected material has a vast variation. These evaluations could assist breeders to select and identify genotypes with desirable characteristics for inclusions in variety breeding programs. © 2011 Academic Journals.
Keywords: Characterization; Cluster; Genotype; Potato; Tuber; Turkey